Proactive Personality, Motivation and Employee Creativity in the Public Sector Hospitals of Peshawar City - Farooq, Naveed; Rehman, Alam; Bilal, Hazrat; Saleem, Kashif; Hussain, Arif; Zeeshan, Muhammad (International Review of Management and Marketing, 2020)
Numerous practitioner-oriented investigations have argued that employees should be more proactive and creative on their jobs, as these behaviors are significant for job performance. Organizational investigations on the antecedents of proactivity and creativity have appeared differently and have explored various approaches in defining, determining and understanding proactivity and creativity. This investigation examines the mediating role of motivation between proactivity and creativity among the doctors in the public sector hospitals. To give a rigorous test of the hypotheses, a grounded study is conducted taking a sample of 220 doctors. The results confirm a positive significant relationship between proactive personality and creativity, and report a significant relationship with motivation too. Additionally, the study demonstrates that motivation does not mediate the relationship of these variables. The study discusses the implications of the findings for enhancing motivation. Keywords: Proactivity, Motivation, Creativity, Doctors JEL Classifications: G22, G12 DOI: https://doi.org/10.32479/irmm.9510